PERTUMBUHAN DAN PRODUKSI MENTIMUN (CUCUMIS SATIVUS L.) PADA PERBEDAAN KONSENTRASI PUPUK CAIR, PEMANGKASAN DAN JARAK TANAM - Tiyandara, Nandia Arti; Oktarina, Oktarina; Wijaya, Insan (University of Prof. Dr. Hazairin, SH, 2020)
This study aims to determine: 1) The effect of liquid fertilizer concentration in increasing the growth and production of cucumbers. 2) The effect of pruning in increasing the growth and production of cucumbers. 3) The effect of different plant spacing in increasing cucumber growth and production. 4) The interaction between liquid fertilizer concentration and pruning in increasing the growth and production of cucumber plants. 5) Interaction between the concentration of liquid fertilizer with differences in spacing in increasing the growth and production of cucumber plants. 6) Interaction between pruning with differences in plant spacing in increasing growth and production of cucumber plants. 7) Interaction between differences in concentration of liquid fertilizer, pruning and spacing in increasing cucumber growth and production. The study was conducted from 28 March to 20 June 2019, at the Experimental Garden of the Faculty of Agriculture, University of Muhammadiyah Jember, with an altitude of 89 meters above sea level. The design used was a Randomized Block Design with 3 factors. The effect of the difference in the concentration of liquid fertilizer (N) was not significantly different except for the variable of flowering age and weight of the plots. The effect of pruning (P) was not significantly different except for the diameter of the stem age of 14 days after planting, the weight of planted fruit and the weight of plots. The effect of plant spacing (J) was not significantly different except for the variable height of the plant at the age of 14 days after planting and the diameter of the stem at the age of 7 days after planting. The interaction effect of liquid fertilizer concentration and pruning (NP) was not significantly different except for variable fruit length and plot weight. The effect of the interaction of liquid fertilizer concentration and plant spacing (NJ) was not significantly different except for variable age of flowering, fruit length and weight of the plot per fruit. The effect of trimming interaction and plant spacing (NJ) differed insignificantly except for variable fruit length and plot weight. The interaction effect of liquid fertilizer concentration, pruning and planting distance (NPJ) was not significantly different except for the variable length of fruit and weight of the plot per plot. The best liquid organic fertilizer concentration is 2ml / l water and 3 ml / l water, the best pruning is pruning 3 branches, and the best spacing is 40cmx60cm.